PERANAN APLIKASI TWITTER ATAU X DALAM INTERAKSI KOMUNIKASI GUNA MEMBANTU PENYEIMBANGAN KESEHATAN MENTAL PADA REMAJA SAAT INI - Kukuh Wijayanti; Qoniah Nur Wijayani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In communication, of course, there must be an interaction carried out by several parties concerned. Communication interactions today are not only done directly or face-to-face. With the development of technology, it also brings progress to the existence of social media. Current interactions can also be done online or online using social media that comes with a wide scope in a very fast time. Apart from having a negative impact, social media also comes with a positive impact. However, as technology advances people begin to lose their sense of sensitivity to their surroundings. Now there is an increase in the number of people with mental disorders in the world. Mental illness is one of the things that is very difficult to overcome because this disease is related to a person's mentality that physically they may look healthy so it is difficult to detect if not with special treatment. Many mental disorders make teenagers their victims. This is usually triggered by a lack of support and feeling alone. And with the existence of social media, it helps teenagers to interact with many people without fear of their identity being spread.